Biologically Inspired and Magnetically Recoverable Copper Porphyrinic Catalysts: A Greener Approach for Oxidation of Hydrocarbons with Molecular Oxygen. (12th February 2016) - Henriques, César A.; Fernandes, Auguste; Rossi, Liane M.; Ribeiro, M. Filipa; Calvete, Mário J. F.; Pereira, Mariette M.
Abstract : An efficient synthetic method for magnetically recoverable hybrid copper porphyrinic nanomaterials is reported. These functionalized magnetic materials prove to be efficient bioinspired oxidation catalysts of olefins and thiols, using molecular oxygen as oxidant, in total absence of reductants and solvents, with the highest TON (turnover number) yet achieved for this reaction (≈200 000). A comparative study between homogeneous and heterogeneous oxidation of cyclohexene is discussed, revealing the heterogeneous system to be the most promising concerning stability and reusability of the catalysts. The full characterization of the magnetic hybrid porphyrinic nanomaterials, by transmission electron microscopy, flame atomic absorption spectrometry, thermogravimetry, N2 sorption, and infrared spectroscopy, is also described. Abstract : An efficient synthetic method for magnetically recoverable hybrid copper porphyrin based nanomaterials is reported. These prove to be stable and reusable efficient bioinspired oxidation catalysts of olefins and thiols, using molecular oxygen as oxidant, in total absence of reductants and solvents, with the highest turnover number yet achieved for this reaction (≈200 000).